Does more mean better? Sibling sex composition and the link between family size and children's quality - Javier E. Baez (Institute for the Study of Labor (IZA), 2008)
Exogenous variation in fertility from parental preferences for sex-mix among their children is used to identify the causal effect of family size on several measures associated with either the allocation of resources towards children within the household or the outcomes of these investments. Results using data from Colombia suggest that family size has negative effects on average child quality. Children from larger families have accumulated almost 1 year less of education, are less likely to enroll in school and about twice as likely to be held back in school. A larger family also increases the likelihood that oldest siblings share a room and reduces the chance that they have access to clean water and sanitary sewer facilities by approximately 15 percentage points, suggesting the existence of negative effects arising from limited household resources. Mothers in these households have less labor participation (over 27 percentage points) and their oldest children are also more likely to engage in labor activities or domestic chores. Children from larger families are also more likely to be physically or psychologically affected by domestic violence within the household. Other less robust but informative calculations using data on anthropometrics, morbidity and immunization records also fit well with the main results of the quasi-experimental research design. The evidence presented here is consistent with the tradeoff between the number and quality of children implied by the theoretical interdependence in their prices and is robust to different specifications, estimation methods and alternative sub-samples.
urn:nbn:de:101:1-2008043023
Keywords: D1; 330; Fertility; household behavior; children's well-being; Colombia; Fruchtbarkeit; Familie; Kinder; Bildungsniveau; Lebensstandard; Kolumbien